2005
DOI: 10.1007/s10909-005-2236-9
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Quantized Vortices in Superfluid Helium and Rotating Bose-Einstein Condensates

Abstract: In this article, we review the research on the dynamics of quantized vortices in superfluid helium and rotating Bose-Einstein condensates with emphasis on the recent research done by our group. A quantized vortex is a topological defect that arises from the order parameter in Bose-Einstein condensation in which frictionless superfluid flows with quantized circulation around each vortex.A quantized vortex was both predicted and discovered first in superfluid 4 He which was the first example of a Bose-Einstein c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 72 publications
0
4
0
Order By: Relevance
“…In laboratory and numerical experiments, it is observed that the vortex tangle is polarized; the average vorticity projected along the rotation axis is not zero (Finne et al 2003;Tsubota et al 2004;Tsubota & Kasamatsu 2005). This is because, under these experimental conditions, one has β 1 > ∼ β 4 v ns /(κΩ 2 ) 1/2 in equation (10), where β 1 is the polarizationinducing term.…”
Section: Glitch: Decay Of the Tanglementioning
confidence: 99%
“…In laboratory and numerical experiments, it is observed that the vortex tangle is polarized; the average vorticity projected along the rotation axis is not zero (Finne et al 2003;Tsubota et al 2004;Tsubota & Kasamatsu 2005). This is because, under these experimental conditions, one has β 1 > ∼ β 4 v ns /(κΩ 2 ) 1/2 in equation (10), where β 1 is the polarizationinducing term.…”
Section: Glitch: Decay Of the Tanglementioning
confidence: 99%
“…This must be valid both in classical and superfluid liquids [14]. What is different is the parameter ǫ: it is determined by the dissipation mechanism which is different in two liquids.…”
Section: Kolmogorov Cascadementioning
confidence: 99%
“…They are well-known objects, studied in detail theoretically and created in experiments, prior to the work on bright vortex solitons. Results obtained for the "dark vortices", starting from the earliest ones [86][87][88], have been collected in many publications dealing with various settings in photonics [89][90][91][92][93][94][95] (including exciton-polariton condensates [96][97][98], where the vortices exist in dissipative media) and BEC [61,[99][100][101][102][103][104][105], as well as in quantum Fermi gases [106,107]; see also book [108] for an overview of the theme. The studies of vortices in this context are also known as "singular optics", with pivots of the vortices considered as singularities of optical fields; many publications on the latter theme were collected in a special issue of Journal of Optics [109] (see also book [110]).…”
mentioning
confidence: 99%